Tuberculosis Prevention and Control Health Worker Training Program in the Border Region of Chiapas, Mexico - Reyes González, Martha Patricia (2014)
Objective: Design and evaluate a community health worker training program with educational and participative elements, for better tuberculosis control in communities with a high incidence of tuberculosis in Chiapas, Mexico. Methods: The training of community health workers in the diagnosis and treatment of tuberculosis was a proposal that came out of a sociocultural needs assessment that used participative workshops to generate a better understanding of the disease, with biomedical and community-based underpinnings. Results: Community participation was essential to reflection and understanding the problem of tuberculosis in the community context as well as possible solutions. It has proven to be an effective form of communication with the community and way of gaining investment in obtaining results in the diagnosis and treatment of the disease. The project was implemented in Verapaz, Tres Maravillas and Nuevo México of Frontera Comalapa Municipality, Chiapas. We found that previous community “participation” in health programs and particularly tuberculosis prevention and control programs had been as passive recipients of informative talks without confirmation of learning. These localities have the highest incidences of tuberculosis in Mexico. The course trained 15 community health workers: 10 from Nuevo Mexico, 4 from Verapaz, and one from Tres Maravillas, who went on to serve their respective community and were well-received by patients and family members. Conclusion: Community participation in order to reflect on and define the problem of tuberculosis as well as possible next steps, proved to be effective in yielding diagnostic and treatment results and improve communication with the community. Impact on knowledge, program planning, population monitoring, and results were evaluated through an output-process-outcomes framework. The training proved efficient and useful in the supervision of tuberculosis treatment at the community level.